Method for manufacturing r-t-b-based sintered magnet
The method for manufacturing R-T-B sintered magnets by controlling the content of B and C and using specific diffusion sources addresses the challenges of thermal demagnetization and resource limitations, resulting in improved magnetic properties.
Patent Information
- Application Number
- JP2024144471
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-29
- Filing Date
- 2024-08-26
- Publication Date
- 2025-04-10
AI Technical Summary
R-T-B sintered magnets face challenges with irreversible thermal demagnetization at high temperatures, requiring high coercive force, and the substitution of light rare earth elements with heavy rare earth elements improves coercivity but reduces residual magnetic flux density and is limited by resource availability and price instability.
A method for manufacturing R-T-B sintered magnets involves controlling the total content of boron (B) and carbon (C) to achieve grain boundary reforming, using a diffusion source of RL-C-A alloy to adjust the content when it is below a predetermined value, and diffusing RL and A from a separate source when the content exceeds this value.
This method effectively improves the magnetic properties of R-T-B sintered magnets by enhancing coercivity and maintaining residual magnetic flux density, while also addressing the resource and cost limitations associated with heavy rare earth elements.
Smart Images

Figure 2025060426000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing an RTB based sintered magnet. [Background technology]
[0002] RTB sintered magnets (R is a rare earth element containing at least one selected from the group consisting of Nd, Pr and Ce, T is an element containing at least one selected from the group consisting of Fe, Co, Al, Mn and Si, and the mass ratio of T is 90% or more Fe, and B is boron) are known as the most high-performance magnets among permanent magnets, and are used in various motors such as motors for electric vehicles (EV, HV, PHV, etc.), motors for industrial equipment, and home appliances. RTB sintered magnets are mainly composed of R 2 T 14 It is composed of a main phase made of B compounds and a grain boundary phase (hereinafter sometimes simply referred to as "grain boundary") located at the grain boundary portion of this main phase. 2 T 14 The B compound is a ferromagnetic phase with high magnetization.
[0003] RTB sintered magnets have a coercive force H cJ (Hereinafter, simply "coercive force" or "H cJ This causes a problem of irreversible thermal demagnetization, as the magnetization temperature drops and the magnetization rate drops. For this reason, RTB sintered magnets, which are used in electric vehicle motors in particular, have a high H cJ It is required that the applicant have:
[0004] In RTB sintered magnets, R 2 T 14 When a part of the light rare earth elements (mainly Nd and / or Pr) contained in R in the B compound is replaced with heavy rare earth elements (mainly Dy and / or Tb), H cJ It is known that the H cJ will improve.
[0005] However, R 2 T 14When the light rare earth elements in the B compound are replaced with heavy rare earth elements, the H of the RTB sintered magnet cJ While the residual magnetic flux density B r (Hereinafter, simply "B r In addition, heavy rare earth elements, especially Dy, are scarce and have limited production areas, so their supply is unstable and their prices fluctuate greatly. For this reason, in recent years, users have been promoting the use of H as little as possible without using heavy rare earth elements. cJ There is a need to improve this.
[0006] Patent Document 1 discloses an RTB sintered magnet with increased coercivity while reducing the Dy content. The composition of this sintered magnet is limited to a specific range in which the amount of B (boron composition ratio or boron concentration) is relatively low compared to commonly used RTB alloys, and contains one or more metallic elements selected from Al, Ga, and Cu. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2013 / 008756 Summary of the Invention [Problem to be solved by the invention]
[0008] As described in Patent Document 1, the content of heavy rare earth elements is reduced while maintaining high B r and high H cJ In order to realize an RTB sintered magnet with this property, technology for controlling the thickness of the two-particle grain boundary by relatively reducing the amount of B (grain boundary modification technology) is being investigated.
[0009] The modification of the grain boundaries is affected not only by the amount of B, but also by the amount of carbon (C), which functions equivalently to boron (B). Therefore, it is desirable to accurately control the amount of C. However, the amount of C is easily fluctuated due to variations in the amount of C introduced from organic materials (such as powder lubricants) used during the production of RTB sintered magnets.
[0010] The method of manufacturing an RTB based sintered magnet disclosed herein makes it possible to control the combined content of B and C, which are prone to change during the process of manufacturing an RTB based sintered magnet material, and thereby achieve the grain boundary modification necessary to improve the magnetic properties. [Means for solving the problem]
[0011] In an exemplary embodiment, a method for producing an RTB system sintered magnet according to the present disclosure includes the steps of: preparing a plurality of RTB system sintered magnet materials (R is a rare earth element including at least one selected from the group consisting of Nd, Pr, and Ce; T is an element including at least one selected from the group consisting of Fe, Co, Al, Mn, and Si; the mass ratio of T is 90% or more of Fe; and B is boron); preparing an RL-CA alloy diffusion source (RL is a light rare earth element including at least one selected from the group consisting of Nd, Pr, and Ce; C is carbon; and A is an element including at least one selected from the group consisting of Cu, Fe, Co, Ni, Al, Ag, Zn, Si, Sn, Ga, and B); determining a total content of B and C in some of the plurality of RTB system sintered magnet materials; and, if the total content is equal to or less than a predetermined value, diffusing RL, C, and A from the diffusion source into the plurality of RTB system sintered magnet materials. Effect of the Invention
[0012] The method for producing an RTB based sintered magnet disclosed herein makes it possible to control the combined content of B and C, which are easily changed during the process of producing an RTB based sintered magnet material, and thereby realize the grain boundary modification necessary for improving the magnetic properties. [Brief description of the drawings]
[0013] [Figure 1A] FIG. 2 is a schematic diagram showing the main phase and grain boundary phase of an RTB based sintered magnet. [Figure 1B] FIG. 1B is a further enlarged schematic diagram of the dashed rectangular area in FIG. 1A. [Diagram 2] 1 is a flowchart outlining a method for producing an RTB based sintered magnet according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, an embodiment of the present disclosure will be described with respect to an RTB based sintered magnet.
[0015] Conventionally, in an RTB sintered magnet, for example, when (1) the content of R (R is a rare earth element including at least one selected from the group consisting of Nd, Pr, and Ce) is 27% by mass or more and 34% by mass or less of the entire RTB sintered magnet, (2) T is an element including at least one selected from the group consisting of Fe, Co, Al, Mn, and Si, and the mass ratio of T is 90% or more of Fe, and (3) the molar ratio of T to B ([T] / [B]) is more than 14.0 and 15.0 or less, an element such as Ga is added to thicken the two-particle grain boundary and reduce H. cJ It is known that it is possible to improve
[0016] The molar ratio of T to B ([T] / [B]) is the ratio (a / b) of the number of moles (a) obtained by dividing the analytical value (mass%) of the concentration of each element (Fe and at least one of Co, Al, Mn, and Si) constituting T by the atomic weight of each element, to the number of moles (b) obtained by dividing the analytical value (mass%) of the concentration of B by the atomic weight of B.
[0017] When the molar ratio of T to B ([T] / [B]) exceeds 14.0, the B content is R 2 T 14 This means that the stoichiometric composition ratio of the main phase (R 2 T 14The amount of B is reduced relative to the amount of T used to form the compound (B).
[0018] Next, the basic structure of an RTB based sintered magnet will be described.
[0019] RTB sintered magnets have a structure in which the powder particles of the raw material alloy are bonded together by sintering, and are mainly composed of R 2 T 14 It is composed of a main phase made of B compounds and a grain boundary phase located at the grain boundaries of this main phase.
[0020] FIG. 1A is a schematic diagram showing the main phase and grain boundary phase of an RTB sintered magnet, and FIG. 1B is a schematic diagram further enlarging the dashed rectangular area in FIG. 1A. In FIG. 1A, an arrow with a length of 5 μm is shown as an example for reference, showing the reference length of the size. As shown in FIG. 1A and FIG. 1B, an RTB sintered magnet is mainly composed of R 2 T 14 The grain boundary phase 14 is composed of a main phase 12 made of a B compound and a grain boundary phase 14 located at the grain boundary portion of the main phase 12. As shown in FIG. 1B, the grain boundary phase 14 is composed of two R 2 T 14 B compound grains (grains) are adjacent to each other in the two-particle grain boundary phase 14a, and three or more R 2 T 14 The B compound grains include adjacent grain boundary triple junctions 14b.
[0021] R, which is the main phase 12 2 T 14 The R B compound is a ferromagnetic phase with high saturation magnetization and anisotropic magnetic field. Therefore, in RTB sintered magnets, the R 2 T 14 By increasing the proportion of B compounds, r It can improve R 2 T 14 In order to increase the ratio of B compounds, the amounts of R, T, and B in the raw alloy should be adjusted to R 2 T 14 It is best to approach the stoichiometric ratio of the B compound (R amount:T amount:B amount = 2:14:1). 2 T 14When the amount of B or R for forming the B compound is less than the stoichiometric ratio, the grain boundary phase 14 generally contains an Fe phase or an R phase. 2 T 17 Soft magnetic phases such as H cJ However, the amount of B is R 2 T 14 When the amount of the B compound is less than the stoichiometric ratio and at least one selected from the group consisting of Cu, Ga, Ni, Ag, Zn, and Sn is contained, R 2 T 17 The grain boundaries become thicker due to the formation of transition metal-rich phases (e.g., RT-Ga phases) at the grain boundaries from the phase, resulting in high H cJ can be obtained.
[0022] <Embodiment> Next, an outline of the manufacturing method of the RTB based sintered magnet of this embodiment will be described with reference to Fig. 2. As shown in Fig. 2, the manufacturing method of the RTB based sintered magnet of this embodiment includes a step (S10) of preparing a plurality of RTB based sintered magnet materials, a step (S20) of preparing a first diffusion source of an RL-A alloy and a second diffusion source of an RL-CA alloy, and a step (S30) of determining the total content of B and C in at least one of the plurality of RTB based sintered magnet materials (for at least some of the plurality of RTB based sintered magnet materials). Hereinafter, for the sake of explanation, the diffusion source may be referred to as a first diffusion source and a second diffusion source, but both are diffusion sources used for diffusing the sintered magnet material.
[0023] The manufacturing method of the RTB system sintered magnet disclosed herein also includes a step (S40) of diffusing RL and A from a first diffusion source into the plurality of RTB system sintered magnets when the total content of B and C exceeds a predetermined value, and diffusing RL, C, and A from a second diffusion source into the plurality of RTB system sintered magnets when the total content of B and C is equal to or less than the predetermined value. The total content of B and C is determined by measuring B by inductively coupled plasma optical emission spectroscopy (ICP-OES) and measuring C by a gas analyzer using a combustion-infrared absorption method, and the total values of the measured B and C are calculated as the total content of B and C.
[0024] In a preferred embodiment, the above-mentioned "predetermined value" is set to 1.000 mass %, or in a range of 1.000 mass % or less, for example, 0.980 mass %.
[0025] The composition of the RTB based sintered magnet material is preferably R:26.5~30.5% by mass, B: 0.85~0.90% by mass, T: 61.5% by mass or more, Tb: 0.30% by mass or less, and Dy: 0.30% by mass or less and the molar ratio of T to B, [T] / [B], is greater than 14.0.
[0026] Also, preferably, the composition of the first diffusion source is RL: 60~94.5% by mass, Cu: 5~20% by mass, A other than Cu: 0 to 20 mass% It is.
[0027] Also, preferably, the composition of the second diffusion source is RL: 60~94.5% by mass, Cu: 5~20% by mass, C: 0.05~1.0% by mass, A other than Cu: 0 to 20 mass% It is.
[0028] Each of the above steps will now be described.
[0029] <Step of Preparing Multiple RTB-Based Sintered Magnet Materials (S10)> In this embodiment, a step S10 is carried out to form rare earth alloy powder using a jet mill pulverizer as a step (fine pulverization step) of pulverizing the raw alloy to obtain rare earth alloy powder. Prior to step S10, a hydrogen pulverization step is preferably carried out to prepare coarsely pulverized rare earth alloy powder. Here, the composition of the rare earth alloy raw alloy is as follows. R: 26.5 to 30.5 mass% (R is a rare earth element including at least one selected from the group consisting of Nd, Pr, and Ce), M: 0.20 to 1.50 mass% (M is at least one selected from the group consisting of Ga, Cu, Zn, Al, and Si, and must contain Cu); B: 0.85~0.95% by mass, T: 61.5 mass% or more (T is an element containing at least one selected from the group consisting of Fe, Co, Al, Mn, and Si, and the mass ratio of T is Fe at least 90%), At least one selected from the group consisting of Cu, Ga, Ni, Ag, Zn, and Sn; Contains The molar ratio of T to B, [T] / [B], is greater than 14.0.
[0030] It is preferable that the following conditions are also satisfied. Tb: 0.30 mass% or less, and Dy: 0.30 mass% or less
[0031] The rare earth-based raw alloy having the above composition can be produced, for example, by a strip casting method, etc. The rare earth-based alloy may contain a plurality of types of alloy components having different compositions.
[0032] The hydrogen pulverization process may include a hydrogen absorption process in which hydrogen is absorbed into the rare earth alloy at a temperature of 200°C or less in a treatment chamber, and a dehydrogenation process in which hydrogen is exhausted from inside the treatment chamber and the rare earth alloy is heated to a temperature in the range of, for example, 80°C or more and 650°C or less to perform a dehydrogenation process and produce a coarsely pulverized powder.
[0033] The average particle size of the coarsely pulverized powder is, for example, 10 μm or more and 500 μm or less. The average particle size (d50) in the present specification can be measured by an airflow dispersion laser diffraction method (based on JIS Z 8825: revised in 2013). That is, in this specification, the average particle size means the particle size (median diameter: d50) at which the cumulative particle size distribution (volume basis) from the small particle size side is 50%.
[0034] In the fine pulverization step, the coarsely pulverized powder is pulverized to obtain a fine powder having a median diameter d50 of, for example, 3.5 μm or less. The fine pulverization step may include a step of mixing an organic grinding aid with the coarsely pulverized powder. An example of the organic grinding aid is zinc stearate. The average particle size d50 of the finely pulverized powder is preferably 2.0 μm or more and 3.5 μm or less.
[0035] Next, a powder compact is produced from the finely pulverized powder by, for example, pressing in a magnetic field. In the case of pressing in a magnetic field, it is preferable to form the powder compact by pressing in an inert gas atmosphere or by wet pressing from the viewpoint of suppressing oxidation. In particular, in the case of wet pressing, the surfaces of the particles constituting the powder compact are covered with a dispersant such as an oil agent, suppressing contact with oxygen or water vapor in the air. Therefore, it is possible to prevent or suppress oxidation of the particles by the air before, during, or after the pressing process.
[0036] When wet pressing in a magnetic field is performed, a slurry is prepared by mixing the finely pulverized powder with a dispersion medium, and the slurry is supplied to a cavity in a mold of a wet pressing apparatus and press-molded in a magnetic field. The dispersion medium is a liquid in which the alloy powder is dispersed to obtain a slurry. A preferred dispersion medium used in the present disclosure can be mineral oil or synthetic oil. Although the type of mineral oil or synthetic oil is not specified, if the kinetic viscosity at room temperature exceeds 10 cSt, the increased viscosity may strengthen the bonding force between the alloy powders, which may adversely affect the orientation of the alloy powder during wet pressing in a magnetic field. For this reason, the kinetic viscosity of the mineral oil or synthetic oil at room temperature is preferably 10 cSt or less. Furthermore, if the fractional point of the mineral oil or synthetic oil exceeds 400°C, it becomes difficult to remove the oil after obtaining a molded body, and the amount of residual carbon in the sintered body may increase, resulting in a deterioration of the magnetic properties. Therefore, the fractional point of the mineral oil or synthetic oil is preferably 400°C or less. Vegetable oil may also be used as the dispersion medium. Vegetable oil refers to oil extracted from plants, and the type of plant is not limited to a specific plant.
[0037] The obtained alloy powder is mixed with a dispersion medium to obtain a slurry. The mixing ratio of the alloy powder and the dispersion medium is not particularly limited, but the concentration of the alloy powder in the slurry is preferably 70% or more (i.e., 70% by mass or more) in terms of mass ratio. 3 This is because, at a flow rate of 1000 / s, the alloy powder can be efficiently supplied into the cavity and excellent magnetic properties can be obtained. The concentration of the alloy powder in the slurry is preferably 90% or less by mass ratio. The method of mixing the alloy powder and the dispersion medium is not particularly limited. The alloy powder and the dispersion medium may be prepared separately, and then the alloy powder and the dispersion medium may be weighed and mixed in a predetermined amount. In addition, when obtaining the alloy powder by dry-pulverizing the coarsely pulverized powder with a jet mill or the like, a container containing the dispersion medium may be placed at the alloy powder outlet of the pulverizing device such as a jet mill, and the alloy powder obtained by pulverization may be directly collected in the dispersion medium in the container to obtain the slurry. In this case, it is preferable that the atmosphere inside the container is also made of nitrogen gas and / or argon gas, and the obtained alloy powder is directly collected in the dispersion medium without being exposed to the air to obtain the slurry. Furthermore, it is also possible to obtain a slurry consisting of the alloy powder and the dispersion medium by wet-pulverizing the coarsely pulverized powder while it is held in the dispersion medium using a vibration mill, ball mill, attritor, or the like to obtain a slurry consisting of the alloy powder and the dispersion medium.
[0038] The slurry thus obtained can be molded in a known wet press to obtain a molded body having a desired size and shape. The molded body is sintered to obtain a sintered body. The powder molded body may also be molded in a dry press.
[0039] Next, the powder compact is sintered to obtain an RTB based sintered magnet material (sintered body). The powder compact is preferably sintered at a pressure of 0.13 Pa (10 -3 Torr) or less, preferably 0.07 Pa (5.0 x 10 -4 The sintering is carried out under a pressure of 1000 to 1150 Torr or less at a temperature in the range of 1000° C. to 1150° C. In order to prevent oxidation due to sintering, the residual gas in the atmosphere may be replaced with an inert gas such as helium or argon.
[0040] <Step of preparing a diffusion source (S20)> In this embodiment, the RL-A alloy as the first diffusion source and the RL-CA alloy as the second diffusion source are prepared as the diffusion source. In each of the RL-A alloy as the first diffusion source and the RL-CA alloy as the second diffusion source, RL is a light rare earth element including at least one selected from the group consisting of Nd, Pr, and Ce, and A is an element including at least one selected from the group consisting of Cu, Fe, Co, Ni, Al, Ag, Zn, Si, Sn, Ga, and B. By including A in the diffusion source together with RL, the temperature at which the liquid phase is generated is often lowered. This allows the processing temperature during diffusion to be lowered, and the wettability of the liquid phase is improved, making it easier to diffuse the diffusion source into the sintered body. In the RL-A alloy as a whole or the RL-CA alloy, it is preferable that the composition ratio of RL is 80 mass% or more and 94.5 mass% or less of the total, the composition ratio of A is 0 mass% or more and 5 mass% or less of the total, the composition ratio of Cu is 5 mass% or more and 15 mass% or less of the total, and the composition ratio of C is 0.2 mass% or more and 1.0 mass% or less of the total.
[0041] These diffusion sources can be prepared by using a method for producing raw alloys that is employed in general manufacturing methods such as Nd-Fe-B sintered magnets, such as die casting, strip casting, single roll super-quenching (melt spinning), and atomization. The diffusion source may be an alloy obtained by the above method, which has been pulverized by a known pulverizing means such as a pin mill. In order to improve the pulverizability of the alloy obtained by the above method, the alloy may be heat-treated in a hydrogen atmosphere at 700°C or less to incorporate hydrogen, and then pulverized.
[0042] <Step (S40) of determining the total content of B and C in at least one of the plurality of RTB based sintered magnet materials> From the multiple RTB based sintered magnet materials produced by the above method, one of the RTB based sintered magnet materials is sampled, and the total contents of B and C in that RTB based sintered magnet material are measured. B can be measured using inductively coupled plasma optical emission spectroscopy (ICP-OES), and C can be measured using a gas analyzer that uses the combustion-infrared absorption method.
[0043] <Step of diffusing from the diffusion source into the RTB sintered magnet material (S40)> If the total content of B and C in the RTB based sintered magnet material selected as the measurement target exceeds a predetermined value (e.g., 0.980 mass%), a step of diffusing RL and A from a first diffusion source into a plurality of RTB based sintered magnet materials is performed. If the total content of B and C is equal to or less than the predetermined value, a step (S40) of diffusing RL, C, and A from a second diffusion source into a plurality of RTB based sintered magnet materials is performed. Since the second diffusion source contains carbon (C), C is introduced into the RTB based sintered magnet material in the diffusion step. As will be described later, the results of experiments by the present inventors have shown that by using the second diffusion source containing carbon, it is possible to increase the total amount of B and C that is insufficient in the RTB based sintered magnet. It has also been confirmed that C introduced into the RTB based sintered magnet material by diffusion contributes to improving the magnetic properties.
[0044] In these diffusion processes, heat treatment is performed in a vacuum or inert gas atmosphere at a temperature of 700°C to 1100°C. If the heat treatment temperature for diffusion is less than 700°C, the diffusion is insufficient and a high H cJ On the other hand, if the temperature exceeds 1100℃, abnormal grain growth of the main phase occurs, and H cJ The heat treatment temperature for diffusion is preferably 800°C or higher and 1000°C or lower. cJThis is because it is possible to obtain the above. The heat treatment time is set to an appropriate value depending on the composition and dimensions of the sintered body material and the diffusion source, the heat treatment temperature, etc., and is preferably 5 minutes to 30 hours, more preferably 10 minutes to 25 hours, and even more preferably 30 minutes to 20 hours. It is also preferable to prepare the diffusion source in an amount of 1 mass % to 30 mass % of the weight of the sintered body material. If the diffusion source is less than 1 mass % of the weight of the sintered body material, H cJ On the other hand, if it exceeds 30 mass%, B r may decrease.
[0045] The heat treatment for diffusion can be performed using a known heat treatment method. For example, the surface of the sintered body material can be covered with a powder layer of the diffusion source, and the first heat treatment can be performed. For example, the diffusion source can be coated on the surface of the sintered body material by a sputtering method, and then the first heat treatment can be performed. For example, a slurry in which the diffusion source is dispersed in a dispersion medium can be applied to the surface of the sintered body material, and the dispersion medium can be evaporated to bring the diffusion source into contact with the sintered body material. Examples of the dispersion medium include alcohol (ethanol, etc.), NMP (N-methylpyrrolidone), aldehydes, and ketones.
[0046] After the diffusion step, a heat treatment is performed at a temperature of 400°C to 530°C for 30 minutes to 300 minutes. This allows an RTB based sintered magnet to be obtained. This heat treatment is preferably performed in a heat treatment furnace (heat treatment chamber) filled with a vacuum or inert gas atmosphere. The heat treatment may be a multi-stage heat treatment at different temperatures. This heat treatment creates R at the grain boundaries. 6 T 13 The formation of RTA phases such as Ga phases progresses, improving HcJ. EXAMPLES
[0047] The present disclosure will be described in more detail with reference to examples, but the present disclosure is not limited thereto.
[0048] Experimental Example 1 First, the raw materials of each element were weighed so that the RTB sintered magnet material had the composition shown in Table 1, and an alloy was produced by strip casting. The remainder was Fe. The obtained alloy was coarsely pulverized by hydrogen pulverization to obtain a coarsely pulverized powder. Next, zinc stearate was added as a lubricant to the obtained coarsely pulverized powder in an amount of 0.04 mass% relative to 100 mass% of the coarsely pulverized powder, and after mixing, it was dry-pulverized in a nitrogen gas flow using an airflow pulverizer (jet mill device). The average particle size d50 of the finely pulverized powder was 3.0 μm.
[0049] [Table 1]
[0050] Next, 0.4 to 2.0 mass% of lubricant was added to the alloy powder with respect to 100 mass% of the finely pulverized powder, mixed, and then compacted in a magnetic field to obtain compacts with different amounts of lubricant added. The compacting device used was a so-called perpendicular magnetic field compacting device (horizontal magnetic field compacting device) in which the magnetic field application direction and the pressure direction are perpendicular to each other.
[0051] The obtained powder compact was sintered in a vacuum at 1060°C for 4 hours to obtain a plurality of RTB based sintered magnet materials. The density of the obtained RTB based sintered magnet materials was 7.5 Mg / m 3 That was all.
[0052] The results of the components of the obtained RTB based sintered magnet material are shown in Table 1. Each component in Table 1 was measured using inductively coupled plasma optical emission spectroscopy (ICP-OES).
[0053] The boron (B) and carbon (C) contents were measured to determine the total B and C content. C was measured using a gas analyzer that uses the combustion-infrared absorption method. The results are shown in Table 2. Since the amount of carbon (C) was adjusted by changing the amount of lubricant added, when the orientation degree of each sintered body was checked, it was confirmed that the same degree of orientation was obtained for all samples (orientation degree of about 99%).
[0054] [Table 2]
[0055] In Nos. 1, 3, and 4, the total content of B and C was equal to or less than the specified value (0.980% by mass), whereas in No. 2, it exceeded the specified value.
[0056] The RTB sintered magnet materials No. 1 to No. 4 were cut and all surfaces were ground to produce cubic samples measuring 7.2 mm x 7.2 mm x 7.2 mm. Powder of diffusion source SA1 (first diffusion source) (Pr: 90 mass%, Cu: 10 mass%) was then applied to the surface, and a diffusion process was then carried out at 900°C for 600 minutes.
[0057] In addition, a powder of diffusion source SA2 (second diffusion source) (Pr: 89.95% by mass + C: 0.5% by mass + Cu: 9.95% by mass) was applied to the surface of each of the separately prepared RTB based sintered magnet materials No. 1 to No. 3, and a powder of diffusion source SA3 (second diffusion source) (Pr: 89.10% by mass + C: 0.8% by mass + Cu: 9.90% by mass) was applied to the surface of the separately prepared RTB based sintered magnet material No. 4, and then a diffusion process was carried out at 900°C for 600 minutes.
[0058] The weight of the diffusion source powder applied to the surface of each RTB based sintered magnet material was 3.0 mass% relative to 100 mass% of the RTB based sintered magnet material. The diffusion source powders of the diffusion sources SA1 to SA3 were all adjusted to 106 μm or less by sieving.
[0059] The sintered bodies after the diffusion treatment were heat-treated in a vacuum heat treatment furnace at 460°C in a reduced pressure argon atmosphere controlled at 100 Pa to obtain RTB sintered magnets. The entire surface of each RTB sintered magnet after the heat treatment was ground using a surface grinder to produce cubic samples of 7.0 mm x 7.0 mm x 7.0 mm. The residual magnetic flux density Br and coercive force H were measured using a BH tracer. cJ , H k , H k / H cJThe components of the diffusion sources SA1 to SA3 used and the analysis results of C are shown in Table 3, and the magnetic properties of the obtained diffusion materials are shown in Table 4.
[0060] [Table 3]
[0061] [Table 4]
[0062] As shown in Table 4, Nos. 1, 3, and 4, in which the total content of B and C in the RTB based sintered magnet material is equal to or less than the specified value (0.980 mass%), have improved magnetic properties by diffusing using the second diffusion source compared to diffusing using the first diffusion source. In contrast, No. 2, in which the total content of B and C in the RTB based sintered magnet material is greater than the specified value (0.980 mass%), had roughly the same magnetic properties whether diffused using the first diffusion source or the second diffusion source.
[0063] Experimental Example 2 In the above experimental example 1, when the total content of B and C exceeds a predetermined value, the "predetermined value of the total content of B and C" that is the criterion for determining whether to diffuse RL and A from the first diffusion source into multiple RTB based sintered magnet materials or to diffuse RL, C, and A from the second diffusion source into multiple RTB based sintered magnet materials was set to 0.980 mass%. However, the "predetermined value" is not limited to 0.980 mass%. In this experimental example, the "predetermined value" is set to 1.000 mass%.
[0064] First, the raw materials of each element were weighed so that the RTB sintered magnet material had the composition shown in Table 5, and an alloy was produced by strip casting. The remainder was Fe. The obtained alloy was coarsely pulverized by hydrogen pulverization to obtain a coarsely pulverized powder. Next, zinc stearate was added as a lubricant to the obtained coarsely pulverized powder in an amount of 0.04 mass% relative to 100 mass% of the coarsely pulverized powder, and after mixing, the mixture was dry-pulverized in a nitrogen gas flow using an airflow pulverizer (jet mill device). The average particle size d50 of the finely pulverized powder was 3.0 μm.
[0065] [Table 5]
[0066] Next, 0.4 to 2.0 mass% of lubricant was added to the alloy powder with respect to 100 mass% of the finely pulverized powder, mixed, and then compacted in a magnetic field to obtain compacts with different amounts of lubricant added. The compacting device used was a so-called perpendicular magnetic field compacting device (horizontal magnetic field compacting device) in which the magnetic field application direction and the pressure direction are perpendicular to each other.
[0067] The obtained powder compact was sintered in a vacuum at 1060°C for 4 hours to obtain a plurality of RTB based sintered magnet materials. The density of the obtained RTB based sintered magnet materials was 7.5 Mg / m 3 That was all.
[0068] The results of the components of the obtained RTB based sintered magnet material are shown in Table 5. Each component in Table 5 was measured using inductively coupled plasma optical emission spectroscopy (ICP-OES).
[0069] The boron (B) and carbon (C) contents were measured to determine the total B and C content. C was measured using a gas analyzer that uses the combustion-infrared absorption method. The results are shown in Table 6. Since the amount of carbon (C) was adjusted by changing the amount of lubricant added, when the orientation degree of each sintered body was checked, it was confirmed that the same degree of orientation was obtained for all samples (orientation degree of about 99%).
[0070] [Table 6]
[0071] In Nos. 6, 7, 8, and 9, the total content of B and C was equal to or less than the specified value (1.000% by mass), whereas in No. 5, it exceeded the specified value.
[0072] The RTB sintered magnet materials No. 5 to No. 9 were cut and all surfaces were ground to create cubic samples measuring 7.2 mm x 7.2 mm x 7.2 mm. Powder of the first diffusion source (diffusion source SA4) (Pr: 91.8 mass%, Cu: 9.5 mass%) was then applied to the surface of the samples, and a diffusion process was then carried out at 900°C for 600 minutes.
[0073] In addition, a powder of a second diffusion source (diffusion source SA5) (Pr: 91.4 mass% + C: 0.51 mass% + Cu: 9.6 mass%) was applied to the surface of each of the separately prepared RTB based sintered magnet materials No. 5 to No. 9, and a different amount of powder of the diffusion source SA5 was also applied to the surface of each of the separately prepared RTB based sintered magnet materials No. 5 to No. 9, after which a diffusion process was carried out at 900°C for 600 minutes.
[0074] The weight of the diffusion source powder applied to the surface of each RTB based sintered magnet material was 3.0 mass% for the first diffusion source (SA4) relative to 100 mass% of the RTB based sintered magnet material. In contrast, for the second diffusion source (SA5), experiments were conducted with examples of 3.0 mass% and 4.0 mass% relative to 100 mass% of the RTB based sintered magnet material. The diffusion source powders for diffusion sources SA4 and SA5 were both adjusted to 106 μm or less by sieving.
[0075] The sintered bodies after the diffusion treatment were heat-treated in a vacuum heat treatment furnace at 460°C in a reduced pressure argon atmosphere controlled at 100 Pa to obtain RTB sintered magnets. The entire surface of each RTB sintered magnet after the heat treatment was ground using a surface grinder to produce cubic samples of 7.0 mm x 7.0 mm x 7.0 mm. The residual magnetic flux density Br and coercive force H were measured using a BH tracer. cJ , H k , H k / H cJ The components of the diffusion sources SA4 and SA5 used and the analysis results of C are shown in Table 7, and the magnetic properties of the obtained diffusion materials are shown in Table 8.
[0076] [Table 7]
[0077] [Table 8]
[0078] As shown in Table 8, Nos. 6, 7, 8, and 9, in which the total content of B and C in the RTB based sintered magnet material is equal to or less than the specified value (1.000 mass%), all had improved magnetic properties when diffused using the second diffusion source compared to when diffused using the first diffusion source. In contrast, No. 5, in which the total content of B and C in the RTB based sintered magnet material is greater than the specified value (1.000 mass%), had almost the same magnetic properties whether diffused using the first diffusion source or the second diffusion source, but the magnetic properties were different when diffused using the H k / H cJ In addition, in Nos. 6, 7, 8, and 9, in which the combined content of B and C in the RTB based sintered magnet material was below the specified value (1.000% by mass), a higher coercive force was achieved when the deposition amount of the second diffusion source was 4% by mass rather than 3% by mass.
[0079] From the above experimental examples, the "predetermined value" is preferably 1.000 mass %, more preferably 0.990 mass % because this increases the range of increase in the magnetic properties, and even more preferably 0.980 mass %.
[0080] As described above, the present disclosure includes the methods for producing RTB based sintered magnets described in the following items. [Item 1] preparing a plurality of RTB based sintered magnet materials (R is a rare earth element including at least one selected from the group consisting of Nd, Pr, and Ce, T is an element including at least one selected from the group consisting of Fe, Co, Al, Mn, and Si, the mass ratio of T being 90% or more being Fe, and B being boron); preparing a first diffusion source of an RL-A alloy and a second diffusion source of an RL-CA alloy (wherein RL is a light rare earth element including at least one selected from the group consisting of Nd, Pr, and Ce, C is carbon, and A is an element including at least one selected from the group consisting of Cu, Fe, Co, Ni, Al, Ag, Zn, Si, Sn, Ga, and B); determining the total content of B and C in some of the plurality of sintered RTB magnet materials; a step of diffusing R L and A from the first diffusion source into the plurality of RTB system sintered magnet materials when the total content of B and C exceeds a predetermined value, and diffusing R L, C, and A from the second diffusion source into the plurality of RTB system sintered magnet materials when the total content of B and C is equal to or less than a predetermined value; A method for producing an RTB sintered magnet comprising the steps of: [Item 2] 2. The method for producing an RTB based sintered magnet according to item 1, wherein the predetermined value is 1.000 mass %. [Item 3] The composition of the diffusion source is RL: 60~94.5% by mass, Cu: 5~20% by mass, C: 0.05~1.0% by mass, A other than Cu: 0 to 20 mass% 2. A method for producing an RTB based sintered magnet according to Item 1, [Item 4] 4. The method for producing an RTB based sintered magnet according to any one of items 1 to 3, wherein the predetermined value is 0.980 mass %. [Item 5] preparing a plurality of RTB based sintered magnet materials (R is a rare earth element including at least one selected from the group consisting of Nd, Pr, and Ce, T is an element including at least one selected from the group consisting of Fe, Co, Al, Mn, and Si, the mass ratio of T being 90% or more being Fe, and B being boron); preparing a first diffusion source of an RL-A alloy and a second diffusion source of an RL-CA alloy (wherein RL is a light rare earth element including at least one selected from the group consisting of Nd, Pr, and Ce, C is carbon, and A is an element including at least one selected from the group consisting of Cu, Fe, Co, Ni, Al, Ag, Zn, Si, Sn, Ga, and B); determining the total content of B and C in some of the plurality of sintered RTB magnet materials; a step of diffusing R L and A from the first diffusion source into the plurality of RTB system sintered magnet materials when the total content of B and C exceeds a predetermined value, and diffusing R L, C, and A from the second diffusion source into the plurality of RTB system sintered magnet materials when the total content of B and C is equal to or less than a predetermined value; A method for producing an RTB based sintered magnet comprising the steps of: [Item 6] The composition of the first diffusion source is RL: 60~94.5% by mass, Cu: 5~20% by mass, A other than Cu: 0 to 20 mass% and The composition of the second diffusion source is RL: 60~94.5% by mass, Cu: 5~20% by mass, C: 0.05~1.0% by mass, A other than Cu: 0 to 20 mass% 6. A method for producing an RTB based sintered magnet according to Item 5, wherein [Industrial Applicability]
[0081] The method for producing an RTB based sintered magnet according to the present disclosure can be used to produce permanent magnets for a wide variety of applications, such as voice coil motors (VCMs) for hard disk drives, motors for electric vehicles (EVs, HVs, PHVs), motors for industrial equipment, and other motors, as well as home appliances. [Explanation of symbols]
[0082] 12 Main phase 14 Grain boundary phase 14a Two-particle boundary phase 14b Particle boundary triple point
Claims
1. preparing a plurality of R-T-B based sintered magnet materials (R is a rare earth element including at least one selected from the group consisting of Nd, Pr, and Ce, T is an element including at least one selected from the group consisting of Fe, Co, Al, Mn, and Si, the mass ratio of T being 90% or more of Fe, and B being boron); A step of preparing a diffusion source of an RL-C-A alloy (wherein RL is a light rare earth element including at least one selected from the group consisting of Nd, Pr, and Ce, C is carbon, and A is an element including at least one selected from the group consisting of Cu, Fe, Co, Ni, Al, Ag, Zn, Si, Sn, Ga, and B); determining the total content of B and C in some of the plurality of sintered R-T-B based magnet materials; a step of diffusing RL, C, and A from the diffusion source into the plurality of sintered R-T-B based magnet materials when the total content of B and C is equal to or less than a predetermined value; The method for producing an RTB based sintered magnet includes the steps of:
2. The method for producing a sintered RTB based magnet according to claim 1, wherein the predetermined value is 1.000 mass %.
3. The composition of the diffusion source is RL: 60 to 94.5% by mass, Cu: 5 to 20% by mass, C: 0.05 to 1.0% by mass, A other than Cu: 0 to 20 mass%; The method for producing a sintered RTB based magnet according to claim 1,
4. 2. The method for producing a sintered R-T-B based magnet according to claim 1, wherein the predetermined value is 0.980 mass %.
Citation Information
Patent Citations
Alloy for r-t-b-based rare earth sintered magnet, process for producing alloy for r-t-b-based rare earth sintered magnet, alloy material for r-t-b-based rare earth sintered magnet, r-t-b-based rare earth sintered magnet, process for producing r-t-b-based rare earth sintered magnet, and motor
WO2013008756A1